Inclusify : the power of uniqueness and belonging to build innovative teams - Johnson, Stefanie K. (New York Harper Collins, 2020)
Inclusify reveals the unexpected ways that well-intentioned leaders undermine their teams, explains how to recognize the myths and misperceptions that drive these behaviors, and provides practical strategies to become an Inclusifyer. By learning why uniqueness and belonging are so imperative, leaders can better understand what makes their employees tick and find ways to encourage them to be themselves while ensuring they feel like they are fully part of the group. The result is a fully engaged team filled with diverse perspectives$1 (Bthe key to creating innovative and imaginative ideas that drive value.s
Keywords: Project management; Teams in the workplace; Creative ability in business; Leadership